Institutional ownership and conservatism - Ramalingegowda, Santhosh; Yu, Yong (Journal of Accounting and Economics, 2012)
Recent research suggesting that shareholders demand conservative financial reporting raises the question: Which shareholders demand conservatism? We find that higher ownership by institutions that are likely to monitor managers is associated with more conservative financial reporting. This positive association is more pronounced among firms with more growth options and higher information asymmetry, where direct monitoring is more difficult and the potential governance benefits of conservatism are greater. Further, lead-lag tests of the direction of causality suggest that ownership by monitoring institutions leads to more conservative reporting, rather than the reverse. Collectively, these results are consistent with monitoring institutions demanding conservatism.